2015
DOI: 10.1177/1545968315575613
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Electrical Stimulation for Stroke Rehabilitation

Abstract: The primary analysis pertaining to efficacy of EECS during upper limb motor rehabilitation in chronic stroke patients was negative at 4 weeks postrehabilitation. A better treatment response was observed in a subset of patients eliciting stimulation induced upper limb movements during motor threshold assessments performed prior to each rehabilitation session. Post hoc comparisons indicated treatment effect differences at 24 weeks, with the control group showing significant decline in the combined primary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(92 citation statements)
references
References 54 publications
5
86
0
1
Order By: Relevance
“…For example, deficits in learning and memory in rats after TBI has been improved by theta burst stimulation (TBS) of the fornix and hippocampus (Sweet et al, 2014). There is also human data supporting the use of subthreshold cortical stimulation for recovery after an ischemic infarct (Levy et al, 2008); however, recent data from phase III trials have been negative (Levy et al, 2016). …”
Section: Neurorehabilitation and Electrical Stimulation Of The Nervoumentioning
confidence: 99%
See 1 more Smart Citation
“…For example, deficits in learning and memory in rats after TBI has been improved by theta burst stimulation (TBS) of the fornix and hippocampus (Sweet et al, 2014). There is also human data supporting the use of subthreshold cortical stimulation for recovery after an ischemic infarct (Levy et al, 2008); however, recent data from phase III trials have been negative (Levy et al, 2016). …”
Section: Neurorehabilitation and Electrical Stimulation Of The Nervoumentioning
confidence: 99%
“…Researchers have been dedicated to improving the quality of life for these patients in several ways, e.g., (1) biological manipulation of the cellular milieu to encourage neuronal repair and regeneration (Magavi et al, 2000; Chen et al, 2002; Lee et al, 2004; Freund et al, 2006; Benowitz and Yin, 2007; Park et al, 2008; Maier et al, 2009; de Lima et al, 2012b; Dachir et al, 2014; Li et al, 2015; Omura et al, 2015), (2) creation of neural- or brain-machine interfaces designed to circumvent lesions and restore functionality (Wolpaw and McFarland, 1994; Kennedy and Bakay, 1998; Leuthardt et al, 2004; Monfils et al, 2004; Hochberg et al, 2006, 2012; Moritz et al, 2008; O'Doherty et al, 2009; Ethier et al, 2012; Collinger et al, 2013; Guggenmos et al, 2013; Ifft et al, 2013; Memberg et al, 2014; Zimmermann and Jackson, 2014; Grahn et al, 2015; Jarosiewicz et al, 2015; Soekadar et al, 2015; Bouton et al, 2016; Capogrosso et al, 2016; Donati et al, 2016; Hotson et al, 2016; Rajangam et al, 2016; Vansteensel et al, 2016), and (3) new rehabilitation techniques that include electrical stimulation and pharmacological enhancement of spinal circuitry to stimulate recovery (Carhart et al, 2004; Levy et al, 2008, 2016; Dy et al, 2010; Harkema et al, 2011, 2012; Dominici et al, 2012; van den Brand et al, 2012; Gad et al, 2013b, 2015; Angeli et al, 2014; Gharabaghi et al, 2014a,c; Wahl et al, 2014; Gerasimenko et al, 2015b). Unfortunately, the path to clinical relevance for these individual approaches remains long, and each field tends to operate largely in its own sphere of influence.…”
Section: Introductionmentioning
confidence: 99%
“…88,146 Epidural stimulation of the cortex showed promising initial clinical results, 17,99 but long-term benefits have not been supported when assessed in a large-scale clinical trial (Table 2). 100,124 …”
Section: Neuromodulationmentioning
confidence: 99%
“…Data from clinical trials also suggest that there must be at least minimal capacity for the injured hemisphere to drive motor movements in order for CS to enhance recovery. Despite two early Phase I and II trials that demonstrated potential efficacy of CS in stroke survivors (Brown et al, 2006; Levy et al, 2008a, 2015), a larger Phase III trial failed to show benefit when all study subjects were included in the analysis (Levy et al, 2008b, 2015) although more CS treated subjects maintained improvements at 24 weeks post-treatment compared to controls (Levy). Further, follow-up analysis revealed major motor improvements in a subset of participants in whom CS was delivered in a manner consistent with the parameters found to be effective in the small clinical trials and animal studies (Levy et al, 2015; Plow et al, 2009).…”
Section: Epidural Cortical Stimulation (Cs) Following Strokementioning
confidence: 99%
“…In the Phase I and II studies, movement thresholds were evoked in 75% and 42% of subjects, respectively. In the Phase III study, only 14% of subjects had stimulation-evoked movements in the hand, and it was this subset that had major improvements (Levy et al, 2015). These data suggest that a minimum level of corticospinal integrity is necessary for CS to be effective.…”
Section: Epidural Cortical Stimulation (Cs) Following Strokementioning
confidence: 99%